Detection of peptidoglycan from the gut microbiota governs the lifespan of circulating phagocytes at homeostasis - Hergott,CB; Roche,AM; Tamashiro,E; Clarke,TB; Bailey,AG; Laughlin,A; Bushman,FD; Weiser,JN (Blood, 2016)
Maintenance of myeloid cell homeostasis requires continuous turnover of phagocytes from the bloodstream, yet whether environmental signals influence phagocyte longevity in the absence of inflammation remains unknown. Here, we show that the gut microbiota regulates the steady-state cellular lifespan of neutrophils and inflammatory monocytes, the two most abundant circulating myeloid cells and key contributors to inflammatory responses. Treatment of mice with broad-spectrum antibiotics, or with the gut-restricted aminoglycoside neomycin alone, accelerated phagocyte turnover and increased the rates of their spontaneous apoptosis. Metagenomic analyses revealed that neomycin altered the abundance of intestinal bacteria bearing γ-D-glutamyl-meso-diaminopimelic acid (iE-DAP), a ligand for the intracellular peptidoglycan sensor Nod1. Accordingly, signaling through Nod1 was both necessary and sufficient to mediate the stimulatory influence of the flora on myeloid cell longevity. Stimulation of Nod1 signaling increased the frequency of lymphocytes in the murine intestine producing the pro-inflammatory cytokine interleukin 17A (IL-17A), and liberation of IL-17A was required for transmission of Nod1-dependent signals to circulating phagocytes. Together, these results define a mechanism through which intestinal microbes govern a central component of myeloid homeostasis and suggest perturbations of commensal communities can influence steady-state regulation of cell fate.